Trees of the Central Valley of Costa Rica: reproduction. Indio desnudo. - Rojas-Rodríguez, Freddy (2012)
The following issue presents a brief description about the “indio desnudo” tree (Bursera simaruba (L.) Sarg) including information about its phenology which directly relates to fruit recollection, seed treatment, nursery, and germination processes.